Why scapegoating can ruin an apology: The mediated-moderation model of appropriate crisis response messages in the context of South Korea - Youk, Sungbin; Park, Hee Sun (Frontiers in Psychology, 2023)
Introduction As South Korean companies frequently use apologies for various crisis situations and pair them with other types of crisis response strategies (i.e., scapegoating), theory-driven recommendations for crisis response messages may fall short in practice. This study empirically examines the effectiveness of two crisis response messages (i.e., apology + compensation vs. apology + scapegoating) by integrating the theory of communicative responsibility and situational crisis communication theory. Methods South Korean participants (n = 392) read one of two vignettes: the vignettes described an automobile company’s apology for malfunctioning seat belts which included either compensation or scapegoating. The participant’s perceived communicative responsibility, appropriateness of the apology, and reputation of the company were measured. Process analysis was conducted to examine the mediated-moderation effect of the crisis response messages. Results and Discussion The findings indicate that an apology that is provided with compensation is more appropriate than those with scapegoating. The appropriateness is moderated by the perceived symmetry in communicative responsibility, and fully mediates the relationship between apology type and reputation. This study integrates two theoretical models to examine the mechanism behind the crisis response strategies from the perspective of the message receivers, while considering the cultural and normative context of South Korea.